Historical review of Citrus tristeza virus in Italy - Djelouah K.; Valentini F.; D'Onghia A.M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
A brief introduction on the Italian citrus industry is provided. Tristeza findings are reported from 1955 to date and emphasis is laid on the outbreaks which occurred in Sicily and in Apulia in 2002. Special attention is paid to the Apulian legislation which reinforces the current national regulation for the mandatory control of CTV in Italy.